Pengembangan E-LKPD Berbasis Model Problem Solving untuk Melatihkan Keterampilan Metakognitif Peserta Didik pada Materi Larutan Penyangga - Aida Mustafida A; Utiya Azizah (UNIB Press, 2026)
The purpose of this study is to develop an E-LKPD based on a problem-solving model to train students’ metacognitive skills in the topic of buffer solutions. The metacognitive skills targeted for development are planning, monitoring, and evaluating. The developed E-LKPD was assessed as feasible in terms of validity, practicality, and effectiveness. This study adopted the 4D model (Define, Design, Develop, Disseminate), but its application was limited to the development stage. The research results indicate the following: (1) The validity results obtained a mode of 4, classified as valid; (2) The average percentage of student responses and activities in sessions 1 and 2 were 95% and 97.75%, respectively, and the activity rates for sessions 1 and 2 were 97.75% and 98.33%, respectively, and were classified as very good; (3) The average N-gain score on the metacognitive skills test was 0.74, classified as high. Furthermore, the results of the paired t-test showed a significance value of 0.000; therefore, H0 was rejected and H1 was accepted. From the results described above, it can be concluded that the developed E-LKPD is valid in training students’ metacognitive skills